Feasibility Study of Using New Fuel Composition in IRT-T Research Reactor; Advanced Materials Research : Radiation and nuclear techniques in material science; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Naymushin A. G. Artem Georgievich; Chertkov Yu. B. Yuri Borisovich; Kurganov V. V. Vasiliy Vasilievich; Lebedev I. I. Ivan Igorevich; Mongush S. A.; Daneykina (Daneikina) N. V. Natalia Viktorovna (Nuclear Engineering and Fuel Cycles, 2015)
Title screen